PERAN MEDIA KOMUNIKASI PEMBELAJARAN BAGI ANAK PENYANDANG DISLEKSIA - Ninuk Riswandari; Nurma Yuwita (Program Studi Ilmu Komunikasi, 2021)
The success of the learning process is when students are able to absorb and understand the information provided by educators. However, not all children have normal conditions that are able to absorb all information without any difficulties. For children with dyslexia, the main learning processes related to reading, writing and arithmetic are activities that are quite difficult for them. This disorder is due to congenital biological factors of the child. The sensitivity of teachers and parents in detecting children with dyslexia is very necessary in order to support their growth and development. Because of the learning difficulties experienced by children with dyslexia, media is needed that helps their learning process so that any information conveyed by the teacher can be well received. Media that can be used can be in the form of human-based media, print-based media, audio-based media, or audio-visual-based media. The form of the picture will usually be more easily understood by children with dyslexia.